Disruption of Nuclear Receptor Signaling Alters Triphenyl Phosphate-Induced Cardiotoxicity in Zebrafish Embryos. (24th February 2018) - Mitchell, Constance A; Dasgupta, Subham; Zhang, Sharon; Stapleton, Heather M; Volz, David C
Abstract: Triphenyl phosphate (TPHP) is an unsubstituted aryl phosphate ester used as a flame retardant and plasticizer within the United States. Using zebrafish as a model, the objectives of this study were to rely on (1) mRNA-sequencing to uncover pathways disrupted following embryonic TPHP exposure and (2) high-content screening to identify nuclear receptor ligands that enhance or mitigate TPHP-induced cardiotoxicity. Based on mRNA-sequencing, TPHP exposure from 24 to 72-h postfertilization (hpf) resulted in a concentration-dependent increase in the number of transcripts significantly affected at 72 hpf, and pathway analysis revealed that 5 out of 9 nuclear receptor pathways were associated with the retinoid X receptor (RXR). Based on a screen of 74 unique nuclear receptor ligands as well as follow-up experiments, 2 compounds—ciglitazone (a peroxisome proliferator-activated receptor gamma, or PPARγ, agonist) and fenretinide (a pan-retinoic acid receptor, or RAR, agonist)—reliably mitigated TPHP-induced cardiotoxicity in the absence of effects on TPHP uptake or metabolism. As these data suggested that TPHP may be activating RXR (a heterodimer for both RARs and PPARγ), we coexposed embryos to HX 531—a pan-RXR antagonist—from 24 to 72 hpf and, contrary to our hypothesis, found that coexposure to HX 531 significantly enhanced TPHP-induced cardiotoxicity. Using a luciferase reporter assay, we also found that TPHP did not activate nor inhibit chimeric human RXRα, RXRβ, or RXRγ, suggesting that TPHP does not directly bind nor interact with RXRs. Overall, our data suggest that TPHP may interfere with RXR-dependent pathways involved in cardiac development.